Public family firms and capital structure: A meta-analysis - Christopher Hansen; Joern Block (Corporate Governance: An International Review, 2021)
Research Question/Issue In this study, we examine the impact of family firm status on publicly listed firms' leverage ratios. Furthermore, we investigate the moderating role of a country's institutional setting, especially its shareholder and creditor rights, on this relationship. Research Findings/Insights Conducting a meta-analysis on 869 effect sizes from 613 studies, we find an overall slightly negative but significant relationship between family firm status and leverage. Our results reveal a large amount of heterogeneity and considerable mean effect size differences across the 48 countries included in the study. The results of our meta-regression analysis reveal significant moderating effects of shareholder and creditor rights on family firms' capital structure decisions. Whereas stronger shareholder rights have a positive impact on family firm leverage, stronger creditor rights have a negative impact. Theoretical/Academic Implications Our study combines the two dominating and competing views on family firm leverage. On the one hand, the overall lower leverage ratio of family firms confirms the risk-aversion view of family firms. On the other hand, control considerations also have a significant impact on leverage ratios, as family firms adjust their capital structure dependent on shareholder and creditor rights in their home country. Our study highlights the importance of the institutional setting on firms' financing patterns. Practitioner/Policy Implications The results suggest a significant impact of a country's institutional setting in general, and its strength on shareholder and creditor rights in particular, on family firms' capital structure decisions. Control considerations result in a strategic use of debt financing that ensures the owner family's dominant position in the firm and prevents potentially harmful conflicts with minority shareholders or creditors.
Keywords: 320; Corporate Governance; capital structure; family firms; leverage; meta-analysis